THE ARCHITECTURE OF PEDAGOGY IN THE PRACTICE TEACHING EXPERIENCE (PTE) OF ENGLISH AS A FOREIGN LANGUAGE: A NEW PROPOSAL TO EVALUATE PRACTICUM STUDENTS - Piñeiro Ruiz, Milagro (Universidad de Costa Rica, 2011)
This article attempts to guide supervisors in the development of the Practice Teaching Experience carried out by students of Teaching English as a foreign Language, at the Universidad de Costa Rica, Sede de Occidente. The authors attempt to unify supervising criteria, in order to achieve the highest standard for guiding practicum students throughout parallel procedures.